2000
DOI: 10.1063/1.1290045
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic calibration of thin-film thermocouples by means of a laser modulation technique

Abstract: This article presents static and dynamic calibration methods of thin-film thermocouples ͑TFTCs͒ by means of a laser modulation technique. The static calibration is based on a combined analysis of theoretical and experimental results; knowing the experimental parameters ͑incident laser power, beam waist radius͒, the temperature of the exposed junction is theoretically calculated using a thermal model and the sensor electromotive force ͑emf͒ response is recorded. The ratio between the sensor emf and the correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…The experiments found that the time constants of the sensors were in the range 2.55 ms to 6.24 ms in air, 1.24 ms to 2.37 ms in still water and 1.20 ms to 1.83 ms in stirred water. These results compare favourably with response times measured in FBG based sensors [ 17 , 18 , 35 , 36 ], and to electrical temperature sensors that have been characterized using optical heating methods [ 71 , 73 ]; faster response times have been measured with fibre optic temperature sensors based on silicon FP cavities [ 50 ] and thin-film thermocouples [ 72 ]. The sensor responses to optical heating were also highly repeatable within each sensor, showing impulse response curves having a consistent form and magnitude across multiple laser pulses, and reproducible, with similar measured impulse response curves and time constants across all sensors tested.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The experiments found that the time constants of the sensors were in the range 2.55 ms to 6.24 ms in air, 1.24 ms to 2.37 ms in still water and 1.20 ms to 1.83 ms in stirred water. These results compare favourably with response times measured in FBG based sensors [ 17 , 18 , 35 , 36 ], and to electrical temperature sensors that have been characterized using optical heating methods [ 71 , 73 ]; faster response times have been measured with fibre optic temperature sensors based on silicon FP cavities [ 50 ] and thin-film thermocouples [ 72 ]. The sensor responses to optical heating were also highly repeatable within each sensor, showing impulse response curves having a consistent form and magnitude across multiple laser pulses, and reproducible, with similar measured impulse response curves and time constants across all sensors tested.…”
Section: Discussionsupporting
confidence: 59%
“…A ramped temperature input can also be used for measuring the dynamic temperature response [ 37 , 68 , 70 ]; however, the minimum measurable time constant is limited by the gradient of the ramp [ 68 ]. Other approaches include heat-transfer modelling [ 35 ], and optical heating methods: several investigators have studied the dynamic responses of thermocouples and resistance thermometers using pulsed or modulated light to induce rapid temperature cycles [ 71 , 72 , 73 , 74 , 75 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chohan and coworker measured the time constant of thermocouple using pneumatic cylinder, and the results show that the response time in gas is different from that in water. Serio et al proposed static and dynamic calibration methods of thin‐film thermocouples (TFTCs) by means of a laser modulation technique. The periodic method was used to determine both the frequency response and the 95% response time of Au/Pd TFTC.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, built-in thermal sensors such as resistance temperature detectors (RTD) [ 9 , 10 ], diode sensors [ 11 ], and thin-film thermocouples (TFTCs) [ 12 ] are better candidates. As passive sensors, TFTCs provide stable performance with a short dynamic response time of 10 −9 –10 −6 s [ 13 , 14 , 15 ], unique flexibility in size, and materials [ 12 , 16 , 17 , 18 , 19 ]. In several kinds of TFTCs a moderate thermal power (S) up to 19–26 μV/K and a high temporal resolution of 1–10 mK have been realized [ 12 , 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%